2015
DOI: 10.1002/mrd.22445
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Seq profiling of single bovine oocyte transcript abundance and its modulation by cytoplasmic polyadenylation

Abstract: Molecular changes occurring during mammalian oocyte maturation are partly regulated by cytoplasmic polyadenylation (CP) and affect oocyte quality, yet the extent of CP activity during oocyte maturation remains unknown. Single bovine oocyte RNA sequencing (RNA-Seq) was performed to examine changes in transcript abundance during in vitro oocyte maturation in cattle. Polyadenylated RNA from individual germinal-vesicle and metaphase-II oocytes was amplified and processed for Illumina sequencing, producing approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 65 publications
(85 reference statements)
5
49
0
Order By: Relevance
“…One possibility is that alternate 3′UTRs are utilized for a subset of CCNB1 transcripts allowing for differential regulation of CCNB1 translation (Figure ). Other studies have reported (as do we) a shorter (~33 bp) variant of the bovine CCNB1 3′UTR with a Hex lacking upstream CPE that could explain the early translation of CCNB1 . Alternatively, looking at the sequencing reads mapping to the bovine genome, we found evidence of a third variant of approximately 3000 bp in length containing a multitude of regulatory elements including TCS and MBE (Figure ).…”
Section: Individual Genes Regulated By Cp Activity In Mammalian Oocytessupporting
confidence: 74%
See 3 more Smart Citations
“…One possibility is that alternate 3′UTRs are utilized for a subset of CCNB1 transcripts allowing for differential regulation of CCNB1 translation (Figure ). Other studies have reported (as do we) a shorter (~33 bp) variant of the bovine CCNB1 3′UTR with a Hex lacking upstream CPE that could explain the early translation of CCNB1 . Alternatively, looking at the sequencing reads mapping to the bovine genome, we found evidence of a third variant of approximately 3000 bp in length containing a multitude of regulatory elements including TCS and MBE (Figure ).…”
Section: Individual Genes Regulated By Cp Activity In Mammalian Oocytessupporting
confidence: 74%
“…Complete 3′UTR (those containing a Hex within the last 30 bp) were examined for the presence, position, and distribution of CPE, PBE, and Hex sequences to determine potential cases of CPE‐mediated translational regulation, which we paralleled in human, mouse, and bovine MII oocytes (Table ). Of the 279 and 918 significantly (p‐value < .05 and fold change >2, DESeq) up‐ and downregulated genes with a complete 3′UTR, respectively, 85% of upregulated genes harbored regulatory motifs in line with translational regulation, whereas only 18% of downregulated genes were predicted to be regulated . Interestingly, we also found a tendency for enrichment of motifs within expressed genes at the MII stage in the three species, as suggested by the increased proportion of genes predicted to be regulated among expressed vs. total genes (Table ).…”
Section: Ribonucleic Acid Sequencing Enables Identification Of Candidmentioning
confidence: 52%
See 2 more Smart Citations
“…However, the new era of RNA sequencing aims to the single cell analysis thanks to an amplification step before library preparation, recent examples of which are available in cattle too (Chitwood et al, 2013;Reyes et al, 2015).…”
Section: The Analysis Of Oocyte Transcriptome: From Single Gene To Whmentioning
confidence: 99%